CAPG enhances adipogenesis and inflammatory cytokine expression in adipocytes - Luyao Zhang; Botao Sang; Sainan Li; Ying Li; Dachuan Guo; Qi-Nan Ma; Xiangfei Liu; Xiaoshuo Li; Beidong Chen; Deping Liu (Adipocyte)
The expression of CAPG (capping actin protein, gelsolin-like) is upregulated in visceral white adipose tissue of high-fat diet -fed mice; however, its impact on adipocyte functionality remains unclear. We observed upregulated CAPG expression in the epididymal adipose tissue of high-fat diet-fed mice. To investigate the impact of CAPG on adipocyte differentiation and function, we generated a Capg knockdown 3T3-L1 cell line and induced adipogenic differentiation to mature adipocytes. Adipogenesis was assessed via Oil Red O and BODIPY staining, revealing that Capg knockdown markedly suppressed adipogenesis. Western blot analysis demonstrated that CAPG depletion reduced PPARγ expression. Additionally, Western blot analysis revealed that Capg knockdown significantly enhanced lipid utilization in adipocytes. ELISA and qPCR results further demonstrated that Capg knockdown effectively attenuated inflammatory responses in adipocytes. In conclusion, CAPG promotes adipogenesis and inflammatory responses, suggesting that targeted inhibition of CAPG may represent a potential therapeutic strategy for obesity-associated adipose tissue dysfunction.